THE IMPACT OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION - Sianturi, Charles Makmur; Pasaribu, Vera A. R.; Pasaribu, Romindo M.; Simanjuntak, Juara (SULTANIST: Jurnal Manajemen dan Keuangan, 2022)
AbstractMarketing through social media has been one of trends in recent years in marketing science and practices.  Shifting from conventional marketing tools, marketers have capitalized various tools and means to attract the intention of new customers or to maintain the current customers.  The purpose of this study is to identify the effect of social media marketing on intention to purchase, based on the fact that concept is raising attention of practitioners and researchers.  The object of this study is customers who follow at least one type of social media application in Medan, Indonesia.  The data were collected through self administers questionnaire with 152 respondents. The data is tested with correlation analysis by using SPSS 15.0 version. The results of the study indicated that social media marketing is positively correlated to intention to purchase when social media marketing (1) contain relevant information (2) offer relevant benefits (3) comparable with other products. The results of this study propose several strategies for marketing practitioners